AHMADIYAH DALAM LINGKAR TEOLOGI ISLAM (Analisis Sosial atas Sejarah Munculnya Ahmadiyah) - Moh Muhtador (IAIN Manado, 2018)
Abstrac. This paper specifically discusses the Islamic sects from the social aspect, given the birth of the religious school can not be separated from the social environment. Social behavior has shaped the character in understanding the teachings of religion, thus giving birth to religious streams adapted to the local social context. Therefore, the growth of Islam is part of social interaction and religious teachings that become the repertoire of Islamic theological thought, such as Ahmadiyah. As a religious organization, the birth of Ahmadiyah is not much different from the birth of Shia, Sunni and Khawarij. Given that each sect has a different social character at the beginning of its birth, so does the Ahmadiyya. the sociologically Ahmadiyya is a portrait of the Islamic struggle in India with the surrounding theological character. This study is a research library that aims to analyze the history of Islamic theological thought by using social approach. Hopefully, it can open Islamic discourse related to the birth of sect in Islam, especially Ahmadiyah. Given the birth of a sect is not a religious teaching that comes from God, but part of one's ijtihad in answering social problems in a time. Keywords: Ahmadiyah, Islamic theologi, social Abstrak. Tulisan ini secara khusus mendiskusikan sekte-sekte Islam dari aspek sosial, mengingat lahirnya aliran keagamaan tidak bisa lepas dari lingkungan sosial. Perilaku sosial telah membentuk karakter dalam memahami ajaran agama, sehingga melahirkan aliran-aliran keagamaan yang disesuaikan dengan konteks sosial setempat. Oleh sebab itu, tumbuhnya aliran Islam adalah bagian dari interaksi sosial dan ajaran agama yang menjadi khazanah pemikiran teologi Islam, seperti Ahmadiyah. Sebagai sebuah organisasi keagamaan, lahirnya Ahmadiyah tidak jauh berbeda dengan lahirnya Syiah, Sunni dan Khawarij. Mengingat masing-masing sekte memiliki karakter sosial berbeda pada awal kelahirannya, begitu juga Ahmadiyah. secara sosiologis Ahmadiyah adalah potret dari pergulatan Islam di India dengan karakter teologis yang melingkupi. Kajian ini merupakan library research yang bertujuan untuk menganalisa sejarah pemikiran teologi Islam dengan menggunakan pendekatan sosial. Diharapkan, dapat membuka wacana keislaman terkait dengan lahirnya sekte dalam Islam, terutama Ahmadiyah. Mengingat lahirnya sekte bukan ajaran agama yang datang dari Tuhan, tetapi bagian dari ijtihad seseorang dalam menjawab problem sosial dalam suatu masa. Kata Kunci: Ahmadiyah, teologi Islam, sosial